2007
DOI: 10.1177/0894439306293888
|View full text |Cite
|
Sign up to set email alerts
|

Drop Downs and Scroll Mice: The Effect of Response Option Format and Input Mechanism Employed on Data Quality in Web Surveys

Abstract: Online researchers face whether to use radio buttons or drop downs when presenting respondents with “select one answer from many” questions. However, empirical evidence regarding response effects does not provide direction for favoring one. Using data collected in a New Zealand general population Web survey of 2,400 people, this study contributes to the decision process by investigating format response effects at multiple levels and exploring the potential for input mechanisms to interfere with drop-down answe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…In an empirical study, Healey [16] found that on the single-question level, radio buttons were faster to choose from than drop-down menus, but the use of drop-down menus instead of radio buttons did not affect the overall time to fill in the whole questionnaire. Hogg and Masztal [17] could not find any differences in the time needed to select answers between radio buttons and drop-down menus.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In an empirical study, Healey [16] found that on the single-question level, radio buttons were faster to choose from than drop-down menus, but the use of drop-down menus instead of radio buttons did not affect the overall time to fill in the whole questionnaire. Hogg and Masztal [17] could not find any differences in the time needed to select answers between radio buttons and drop-down menus.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Heerwegh and Loosveldt (2002) found that people needed significantly more time to select options from drop-down menus than from radio buttons, but these findings could not be replicated in a second study. Concerning the drop-out rate, no differences between radio buttons and drop-down menus could be found (Healey, 2007;Heerwegh & Loosveldt, 2002;Hogg & Masztal, 2001). According to Miller and Jarret (2001), radio buttons should be used when two to four options are available; with more than four options they recommend using drop-down menus.…”
Section: Input Typesmentioning
confidence: 98%
“…With the help of the Keystroke-Level Model (Card et al, 1980), it can be theoretically calculated that interaction with a drop-down menu takes longer than interaction with radio buttons, mainly because of the additional click needed to open the drop-down menu. In an empirical study, Healey (2007) found that on the single-question level, radio buttons were faster to choose from than drop-down menus, but the use of dropdown menus instead of radio buttons did not affect the overall time to fill in the whole questionnaire. Hogg and Masztal (2001) could not find any differences in the time needed to select answers between radio buttons and drop-down menus.…”
Section: Input Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to an additional point and click needed to open the dropdown menu. However, in one study the latter hypothesis was confirmed [7] and in another it was rejected [8].…”
Section: Introductionmentioning
confidence: 99%